PENGARUH SOSIALISASI DAN PENERAPAN E-FAKTUR PPN TERHADAP EFISIENSI PENGADMINISTRASIAN FAKTUR PAJAK (Menurut Persepsi Pengusaha Kena Pajak yang Terdaftar di KPP Pratama Banjarmasin) - Indra Saputra (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,This purpose of this study was to found determine whether the socialization variable (X1) and the implementation of e-faktur PPN (X2) have an effect on the Efficiency of Administrative Tax Invoice (Y) according to the Taxpayer Entrepreneur Perception Registered in KPP Pratama Banjarmasin.This study was conducted in Tax Office Pratama Banjarmasin with the number of respondents as many as 95 people. Data analysis was obtained with the help of SPSS version 16 software. The research method used multiple linear regression.The results of this study provide empirical evidence that socialization variables (X1) and the implementation of e-faktur PPN (X2) either partially or simultaneously have a significant effect on the administrative efficiency of tax invoice. e-invoice socialization variables and variables of VAT e-invoice implementation affect the administrative efficiency of tax invoice because it can provide knowledge to the taxable entrepreneur about the benefits, terms and conditions and the procedure of using e-invoice that will streamline the administration of tax invoice.